FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KEDISIPLINAN TENAGA KERJA DI WILAYAH KERJA PUSKESMAS PADANG BULAN KOTA MEDAN - Dewi Purnama; Putranto Manalu (JURNAL KESMAS DAN GIZI (JKG), 2020)
The productivity of the workforce in an organization is influenced by an adequate and clear management system in order to regulate each work process. Improved work motivation for workers / employees, such as providing training and development for workers / employees can be done regularly. This needs to be done to improve the quality, attitude, knowledge, and skills, insight and discipline that are effective and effective, for each employee. The purpose of this study is to determine the factors associated with the level of labor discipline in the working areas Of Padang Bulan Health Center In Medan City. This type of research is descriptive analytic research that is to identify and measure variables using Linear Regression analysis by comparing X2 Count with X2 Table, where if X2 Count > X2 Table then Ho is rejected and Ha is accepted. The results of the study, it was found that there is a very significant (strong) relationship between the relationship of sanctions with the level of labor discipline, where then obtained X2 Count 17.983> X2 Table 3.841, there was a very significant (strong) relationship between the relationship of motivation and the level of labor discipline, where then obtained X2 Count 17.983> X2 Table 3.841, and there is a very significant (strong) relationship between leadership relationship with the level of labor discipline then obtained X2 Count 17.983> X2 Table 3.841. Health workers, especially for supervision from the Head of public health center, are expected to put forward stricter regulations so that sanctions will be obtained by workers to make workers to work better.